The strategic planning process and current practices: A comparative empirical study of UMW Toyota Motor and Chemical Company of Malaysia - Zandi Pour Joopari, GholamReza; Sulaiman, Mohamed; Mohammad Al Atiyat, Hala; Naysary, Babak (Canadian Center of Science and Education, 2013)
This article focuses on the strategic planning process and its best practices that is suggested by the literature and also applied by companies. The two cases studied in this paper are two prominent, non-competing companies operating in Malaysia namely UMW Toyota Sdn. Bhd. and the Chemical Company of Malaysia-Fertilizers Division (CCMFD). Applying a comparative qualitative case study research methodology, the major objective of the study is to investigate in depth the different aspects, processes and practices employed by these well-known companies for their strategic planning processes. Using the grounding theory as a framework of analysis, the research findings revealed common as well as distinctive strategic planning practices between the companies under the study. The output of this project is a set of best practices to strategic planning that are followed by UMW Toyota as well as CCMFD. In the light of the findings of this research and also referring to the literature,some recommendations are made for the best practice of strategic planning process in companies.